2000
DOI: 10.1074/jbc.m000848200
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Cross-linking between the Periplasmic Loop3–4 Regions of PomA, a Component of the Na+-driven Flagellar Motor of Vibrio alginolyticus

Abstract: PomA and PomB form a complex that conducts sodium ions and generates the torque for the Na ؉ -driven polar flagellar motor of Vibrio alginolyticus. PomA has four transmembrane segments. One periplasmic loop (loop 1-2 ) connects segments 1 and 2, and another (loop 3-4), in which cysteine-scanning mutagenesis had been carried out, connects segments 3 and 4. When PomA with an introduced Cys residue (Cys-PomA) in the Cterminal periplasmic loop (loop 3-4 ) was examined without exposure to a reducing reagent, a 43-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…22 -24 Crosslinking studies indicate that periplasmic loop 3 -4 , which joins transmembrane helices 3 and 4, of one PomA subunit is close to loop 3 -4 of an adjacent PomA subunit within the stator complex. 24,25 We have shown that MotA/B from the protondriven motor of Rhodobacter sphaeroides do not complement a DpomAB mutant of V. alginolyticus, 26,27 nor do PomA/B support flagellar rotation without MotX and MotY. However, a DpomABmotXY strain of V. cholerae can swim using E. coli MotA/B and proton motive force.…”
Section: Namentioning
confidence: 99%
“…22 -24 Crosslinking studies indicate that periplasmic loop 3 -4 , which joins transmembrane helices 3 and 4, of one PomA subunit is close to loop 3 -4 of an adjacent PomA subunit within the stator complex. 24,25 We have shown that MotA/B from the protondriven motor of Rhodobacter sphaeroides do not complement a DpomAB mutant of V. alginolyticus, 26,27 nor do PomA/B support flagellar rotation without MotX and MotY. However, a DpomABmotXY strain of V. cholerae can swim using E. coli MotA/B and proton motive force.…”
Section: Namentioning
confidence: 99%
“…It appears that PomA forms a stable homodimer and the two subunits function together (Sato and Homma, 2000b). A periplasmic loop region of PomA is considered important for dimer formation (Yorimitsu et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the molar ratio of MotA to MotB was calculated to be 2:1. Intermolecular cross-linking studies using cysteine substitutions within the periplasmic loop between the third and fourth transmembrane domains of MotA also suggested that adjacent MotA molecules were physically close within the motor (201). To further probe the stoichiometry of the torque generator, a chimeric construct was designed to produce a fused dimer of MotA molecules (158).…”
Section: The Mota-motb Complex Translocates Sodium Ionsmentioning
confidence: 99%